Primary histiocytic sarcoma presenting as diffuse leptomeningeal disease: Case description and review of the literature. Issue 6 (26th May 2017) - Zanelli, Magda; Ragazzi, Moira; Marchetti, Giovanni; Bisagni, Alessandra; Principi, Massimo; Fanni, Daniela; Froio, Elisabetta; Serra, Silvia; Zanetti, Eleonora; De Marco, Loredana; Giangaspero, Felice; Ascani, Stefano
Abstract : Histiocytic sarcoma is a rare malignant neoplasm arising most commonly in lymph nodes, intestinal tract, skin and soft tissue. The incidence of primary CNS histiocytic sarcoma is even rarer with a total of just 27 cases reported in the literature so far. Herein we describe the first autopsy case of histiocytic sarcoma presenting as a diffuse leptomeningeal disease in absence of a CNS tumor‐forming parenchymal lesion. The clinical, pathological and immunophenotypic features are described and an updated literature review on primary CNS histiocytic sarcoma is included.